2016
DOI: 10.1080/00028487.2016.1173095
|View full text |Cite
|
Sign up to set email alerts
|

Low Annual Fidelity and Early Upstream Migration of Anadromous Arctic Char in a Variable Environment

Abstract: The life histories of anadromous Arctic Char Salvelinus alpinus are complex and vary greatly between populations and environments. Here, we detail key aspects of the physical environment and life history of a population of Arctic Char from Nulahugyuk Creek, Nunavut, Canada, to characterize migration traits in a highly variable environment. Over the course of this migration, creek discharge declined precipitously, forcing Arctic Char to migrate through shallow water with large diel temperature fluctuations (>10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 29 publications
2
49
0
Order By: Relevance
“…For example, the Ekalluk River drains the largest lake on Victoria Island, Ferguson Lake, which could offer more abundant or better overwintering habitats, perhaps resulting in lower overwintering mortality. Nonetheless, other studies of Arctic Char have also found spawning habitat accessibility to be a major constraint to migrations (Gilbert et al., ; Gyselman, ), and the easier migrations afforded by the short Ekalluk River constitute a plausible explanation for the observed patterns of dispersal. This hypothesis, however, assumes the ability of Arctic Char to assess which river provides the most readily accessible overwintering habitat.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…For example, the Ekalluk River drains the largest lake on Victoria Island, Ferguson Lake, which could offer more abundant or better overwintering habitats, perhaps resulting in lower overwintering mortality. Nonetheless, other studies of Arctic Char have also found spawning habitat accessibility to be a major constraint to migrations (Gilbert et al., ; Gyselman, ), and the easier migrations afforded by the short Ekalluk River constitute a plausible explanation for the observed patterns of dispersal. This hypothesis, however, assumes the ability of Arctic Char to assess which river provides the most readily accessible overwintering habitat.…”
Section: Discussionmentioning
confidence: 87%
“…when there are no genetic or evolutionary consequences). Accordingly, there is evidence that Arctic Char (and the closely related Dolly Varden; Salvelinus malma ) home to their natal habitats to spawn, but can use non‐natal habitats to overwinter (Armstrong, ; Gilbert et al., ; Gyselman, ; Moore et al., ). Here, we documented the use of alternative freshwater habitats by the same individuals in consecutive years using acoustic telemetry data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…>2°C/hr, Clark et al., ; Clark, Sandblom, Cox, Hinch, & Farrell, ; Penney, Nash, & Gamperl, ; Steinhausen, Sandblom, Eliason, Verhille, & Farrell, ) and at prevailing water temperatures in field studies on wild fish (Farrell et al., ; Rodnick et al., ). Variation in natural temperatures more commonly occurs on diurnal (Gamperl et al., ; Gilbert, Donadt, Swanson, & Tierney, ; Rodnick et al., ) to seasonal scales (Farrell, ; Mathes et al., ), or acutely in an irregular manner as fish transition between different thermal environments such as when moving between the ocean, rivers and lakes (Farrell, ), and when diving (Farrell, ; Friedland et al., ; Rikardsen, Elliott, Dempson, Sturlaugsson, & Jensen, ). The ability of poikilotherms such as salmonids to tolerate and acclimate to warming depends on the rate at which the warming occurs (Dowd, King, & Denny, ; Galbreath, Adams, & Martin, ; Mora & Maya, ).…”
Section: Introductionmentioning
confidence: 99%